The Future of Doctoral Research Challenges and Opportunities - Lee, Anne; Bongaardt, Rob (Taylor & Francis, 2021)
This book explores the future of doctoral research and what it means to be involved in all stages of the process, providing international insights into what's changing, why it's changing and how to work best with these changes. It looks at the key issues that have been thrown into sharp relief by crises such as world pandemics. Drawing on work from outstanding authors, this book shows the ways in which the doctoral process has altered the supervisor/supervisee model and the challenges that now need to be managed, and demonstrates the importance of aligning all the stakeholders, systems and processes to ensure a successful future for doctoral education. Bringing together a range of perspectives, innovative practices and rigorous research, this book tackles topics such as: how doctoral research changes in keeping with the global expansion and transformation of doctoral education programmes the significant influence funding bodies - be they charities, governments, businesses or non-governmental agencies - can have on doctoral research the extent to which doctoral research penetrates daily life and vice versa how to encourage and embed an ethical approach to research, as well as university responses to external challenges. Uniquely international and bringing together the many stakeholders in the research business, this book is essential reading for all doctoral supervisors, candidates and anyone involved in designing or organising research programmes for early career researchers and doctoral students.